2011
DOI: 10.1002/ijc.25927
|View full text |Cite
|
Sign up to set email alerts
|

Head neck squamous cell carcinoma c‐Met+ cells display cancer stem cell properties and are responsible for cisplatin‐resistance and metastasis

Abstract: c-Met, the tyrosine kinase receptor for hepatocyte growth factor, is overexpressed in a variety of tumors in which it plays a central role in malignant transformation. Although c-Met has also been determined to be a critical signaling molecule in normal stem cell function, the potential role of c-Met as a single marker for cancer stem cells (CSCs) has not been previously examined. In our study, we reported that human head neck squamous cell carcinoma (HNSCC) cells expressing c-Met were capable of self-renewal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(109 citation statements)
references
References 46 publications
2
106
1
Order By: Relevance
“…High Met-expression was also detected on populations of cancer stem cells, e.g. in head and neck squamous cell carcinoma 15 . Particularly interesting is the finding that Met and CD44 are stem cell markers on pancreatic carcinoma 16 suggesting that the co-receptor function of CD44 for Met might be of functional importance in these cells.…”
Section: Discussionmentioning
confidence: 96%
“…High Met-expression was also detected on populations of cancer stem cells, e.g. in head and neck squamous cell carcinoma 15 . Particularly interesting is the finding that Met and CD44 are stem cell markers on pancreatic carcinoma 16 suggesting that the co-receptor function of CD44 for Met might be of functional importance in these cells.…”
Section: Discussionmentioning
confidence: 96%
“…Sun and Wang looked at CMET+ cells compared to CMET− and found increased tumorigenicity in a flank injections and found higher percentage of implantation in CMET+ cells compared to CD44+ cells and slightly lower than ALDH+ cells (Sun et al, 2011). In addition, Zhang et al looked at HNSCC cell lines and oral cavity primary tumors identified the presence of SP cells.…”
Section: Tumorigenesismentioning
confidence: 99%
“…Davies et al has shown that HNSCC CD44high cells have greater migration, invasion and metastatic potential compared to CD44low cells (Davis et al, 2010). Gene expression studies comparing ALDH+ cells and ALDH− cells demonstrated elevated levels of the metastatic and epithelial-mesenchymal transition (EMT) biomarkers CMET, TWIST, and SNAIL (Chen et al, 2011;Sun et al, 2011). Zhang et al demonstrated that Side population cells have also been associated with metastasis .…”
Section: Metastasismentioning
confidence: 99%
“…In HNSCC, c-Met+ cells demonstrated self renewal and were able to generate heterogeneous tumours with more tumourigenic potential than by CD44+ marker. Also, c-Met+ /CD44+ combination yielded tumours in 80% of cases, while c-Met+/ALDH1+ displayed tumour formation in 66% cases (Sun and Wang, 2011). Thus c-Met has been proposed as a potent CSC marker in OSCC but further investigation with a greater number of samples and a comparison of c-Met+ with other CSC and stemness markers could give a clear depiction (Sun and Wang, 2011).…”
Section: 8549 Cancer Stem Cells and Stemness Markers In Oral Sccs C-metmentioning
confidence: 99%
“…The resistance to current modalities of treatment such as chemotherapy and radiotherapy is owed to the CSC subpopulation's ability to orchestrate recurrence and facilitate metastasis, which has significant treatment implications (Bradletz et al, 2005;Davis et al, 2010;Sun and Wang, 2011). Hence, CSC hypothesis demands modifications in therapeutic applications & measurement of treatment success.…”
Section: Cancer Stem Cellsmentioning
confidence: 99%